Characterization of submicron aerosol chemical composition and sources in the coastal area of Central Chile. (15th February 2019) - Saarikoski, S.; Reyes, F.; Vázquez, Y.; Tagle, M.; Timonen, H.; Aurela, M.; Carbone, S.; Worsnop, D.R.; Hillamo, R.; Oyola, P.
Abstract: Chemical characteristics and the sources of submicron particles (<1 μm in diameter) were investigated in Valle Alegre, the coastal area of Central Chile. The chemical composition of particles was studied by using a Soot particle Aerosol Mass Spectrometer and Multi-Angle Absorption Photometer. Submicron particles were dominated by organics (42% of mass) and sulfate (39% of mass) while the mass fractions of ammonium, nitrate and black carbon were much smaller (13, 2 and 4% of mass, respectively). Additionally, several metals (V, Zn, Fe, Cd, Cu, K, Na and Mg) were detected in submicron particles and also some of their inorganic salts (e.g. NaCl +, MgCl2 +, CaCl2 +, KCl + and KNO3 + ). The sources of particles were examined by using Positive Matrix Factorization (PMF). Organic aerosol (OA) was divided into five factors by using PMF; hydrocarbon-like OA (HOA), biomass burning OA (BBOA), low-volatility oxygenated OA (LV-OOA), semi-volatile OA (SV-OOA) and marine oxygenated OOA (MOOA). Oxygenated factors (LV-OOA; SV-OOA and MOOA) comprised 75% of total OA with LV-OOA being the dominant factor (38% of OA). Sulfate had two major sources in Valle Alegre; ∼70% of sulfate was related to anthropogenic sources through the oxidation of gas phase SO2 whereas ∼24% of sulfate was associated with biogenic origin related to the oxidation of dimethyl sulfide in the marine environment. Regarding total submicron particle mass (campaign-average 9.5 μg m −3 ), the contribution of anthropogenic sources was at least as large as that of biogenic origin. Highlights: Several areas of Chile have been suffering from poor air quality. Chemistry and sources of particles were examined by aerosol mass spectrometer. Submicron particle mass was dominated by organic compounds and sulfate. Statistical analysis was utilized to identify the origin of organic and sulfate. At least half of the total particle mass was related to anthropogenic sources.